2009
DOI: 10.1123/rsj.33.2.139
|View full text |Cite
|
Sign up to set email alerts
|

What Helps Students Thrive? An Investigation of Student Engagement and Performance

Abstract: Graduation rates, academic success, and health status are top priorities of universities related to student success. Overall it has been found that students academically and socially integrated to the campus are more likely to remain in college and graduate. This article presents a strategy and results of a study that analyzed the overall relationship Student Affairs programs had with student GPA and health status. The goal of this research was to discover what helps students thrive, not just survive at school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…Improvement efforts must be actions designed to create better health. In contrast to pathogenesis, salutogenesis unleashes potential by encouraging actions to improve through the development of new capacities that help move people forward toward desired goals and possibilities as has been seen by students with better academic and health outcomes and working professionals with higher productivity (5,(44)(45)(46)(47)(48)(49).…”
Section: Different Theory Different Methodsmentioning
confidence: 97%
“…Improvement efforts must be actions designed to create better health. In contrast to pathogenesis, salutogenesis unleashes potential by encouraging actions to improve through the development of new capacities that help move people forward toward desired goals and possibilities as has been seen by students with better academic and health outcomes and working professionals with higher productivity (5,(44)(45)(46)(47)(48)(49).…”
Section: Different Theory Different Methodsmentioning
confidence: 97%
“…Researchers found differences in academic success (GPA), psychosocial development, and health status between those who participated in student organizations and those who did not (Abrahamowicz, 1988;Becker, Cooper, Atkins, & Martin, 2009;Foubert & Grainger, 2006). Also, the literature revealed that peers significantly influenced how students spent their time and what students did in college (Kuh, Hu, & Vesper, 2000).…”
Section: Student Developmentmentioning
confidence: 99%
“…The literature demonstrates that through participation in sport clubs, participants acquired specific skills from their involvement and their membership enhanced their college experience (Weis, 2007). (Becker, Cooper, Atkins, & Martin, 2009) To discover what helps students thrive, not just survive at school. To investigate the relationship between student involvement in student affairs functions and student success.…”
Section: Sport Clubsmentioning
confidence: 99%
“…Astin’s (1984, 1993) theory of student involvement established a relationship between participation in intramural sports and exercise with satisfaction and degree attainment (Belch et al, 2001), with as much as 86% of campus recreation facility users who reported participation in extracurricular recreation activities. Intramural sports provided opportunities to be involved and integrated into campus life, leading to social benefits (e.g., friendships, engagement, belonging, increased trust in peers, and enhanced social relationships), cultural benefits (e.g., respect for others, increased understanding and tolerance of different populations, and ability to work with diverse groups), decreased alienation (e.g., integration into social aspects of campus), physical and health benefits (e.g., staying fit, improved fitness, positive feelings of physical well-being, stress reduction, and improved self-confidence), university satisfaction, and academic success (e.g., time management, academic persistence, additional effort to learning, graduate without spending longer than expected in school, and overall educational success; Artinger et al, 2006; Becker et al, 2009; Belch et al, 2001; Forrester, 2015; Henchy, 2011; Lindsey, 2012).…”
mentioning
confidence: 99%
“…Student involvement, success in college, persistence, and retention have an expected relationship with health status and health behaviors inclusive of physical activity and sport participation (Becker et al, 2009). Students without disabilities who engaged more in health behaviors reported higher health status and a better grade point average (GPA).…”
mentioning
confidence: 99%